Fitting the model of Marketing and Increasing the Number of Customers in the Iranian Film Industry - et. al., Morteza Talebi , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Iran is one of the few countries that has had a full cycle of cinematic activities for many years, including production, distribution and screening. Unfortunately, in spite of the very high number of Iranian movies, the number of cinemas, audiences and sales are extremely low. “The economic condition of the Iranian cinema is unfavorable”, “people do not like cinema anymore” and "the Iranian cinema is not yet an industry" are among the statements which are heard a lot in recent years. Many articles and interviews have been published to explain them, but only a few authors and commentators have studied this problem from the market management perspective. In this regard, the present study has conducted to fit the model of marketing and increasing the number of customers in the Iranian film industry.